2003
DOI: 10.1634/stemcells.21-1-15
|View full text |Cite
|
Sign up to set email alerts
|

CD34Hematopoietic Stem Cells: Current Concepts and Controversies

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 56 publications
1
66
0
Order By: Relevance
“…1C and 1F). CD133 was recently identified as a marker for stem cells and progenitor cells (Guo et al, 2003;Lanza et al, 2001). FACS analysis of CD34 + HSCs revealed that the majority of cells were CD133 + (63.9 ± 8.2 %, Figs.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…1C and 1F). CD133 was recently identified as a marker for stem cells and progenitor cells (Guo et al, 2003;Lanza et al, 2001). FACS analysis of CD34 + HSCs revealed that the majority of cells were CD133 + (63.9 ± 8.2 %, Figs.…”
Section: Resultsmentioning
confidence: 98%
“…CD34, a cell-surface sialomucin commonly used for HSC purification, is suggested to play a role in cellular trafficking and migration (Kronenwett et al, 2000). However, CD34 may not be essential for the physiology of HSCs because normal hematopoietic profiles were found in CD34-null mice (Cheng et al, 1996;Guo et al, 2003). Nielsen et al reported recently that CD34 is abundantly expressed in mature mast cells (Nielsen and MaNagny, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In the more differentiated bone marrow cells represented by the CD34 À phenotype, expression levels of the Hox genes are low or absent. In regard to CD34 þ representative of primitive HSCs (Guo et al, 2003), further study demonstrates that Hox genes from clusters A and B are preferentially expressed in the primitive HSC-enriched Sca-1 þ Lin À subpopulation. Their expression is decreased in the HSC-low and depleted subpopulations (Sca-1 þ Lin þ and Sca-1 À Lin þ ) (Pineault et al, 2002).…”
Section: Expression Patterns Of Hox Genes In Hematopoietic Cellsmentioning
confidence: 89%
“…Cells are subjected to Hoechst 33 342 dye staining and fluorescence-activated cell sorting (FACS) analysis; those that actively efflux the Hoechst dye appear as a distinct population of cells on the side of the profile, hence the name 'side population' (SP). The SP phenotype of HSCs in mice and humans is largely determined by the expression of a protein known as the ABCG2 transporter (ATP-binding cassette [ABC] subfamily G member 2, also known as BCRP1) [41,42]. A SP is now recognized in many solid organs, a population enriched for clonogenic activity [43].…”
Section: Cytoprotective Strategiesmentioning
confidence: 99%